Novel Probiotic Bifidobacterium bifidum CECT 7366 Strain Active against the Pathogenic Bacterium Helicobacter pylori - Chenoll, E. (American Society for Microbiology (ASM), 2011)
Helicobacter pylori is considered one of the major risk factors underlying the development of gastritis and gastric and duodenal ulcers. Moreover, 50% of the population carries this bacterium, and consequently, when it is detected, eradication of H. pylori is strongly recommended. Regarding the use of probiotics as functional agents, several studies have shown that there is a direct relationship between the addition of certain probiotic bacteria and in vitro inhibition of H. pylori; however, in vivo studies showing bifidobacterial activity against H. pylori remain scarce. In this study, a Bifidobacterium bifidum strain which proved active in vitro against H. pylori has been isolated, with inhibition levels reaching 81.94% in the case of the supernatant and even 94.77% inhibition for supernatant purified by cationic exchange followed by an inverse phase. In vivo studies using a BALB/c mouse model have proved that this strain partially relieves damage to gastric tissues caused by the pathogen and also decreases the H. pylori pathogenicity ratio. This novel strain fulfills the main properties required of a probiotic (resistance to gastrointestinal juices, biliary salts, NaCl, and low pH; adhesion to intestinal mucus; and sensitivity to antibiotics). Furthermore, the absence of undesirable metabolites has been demonstrated, and its food safety status has been confirmed by acute ingestion studies in mice. In summary, the results presented here demonstrate that Bifidobacterium bifidum CECT 7366 can be considered a probiotic able to inhibit H. pylori both in vitro and in vivo.